2015
DOI: 10.1016/j.ebiom.2015.09.040
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 Defect During Streptococcus pneumoniae Infection Triggers Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Progression of chronic obstructive pulmonary disease (COPD) is linked to episodes of exacerbations caused by bacterial infections due to Streptococcus pneumoniae. Our objective was to identify during COPD, factors of susceptibility to bacterial infections among cytokine network and their role in COPD exacerbations. S. pneumoniae was used to sub-lethally challenge mice chronically exposed to air or cigarette smoke (CS) and to stimulate peripheral blood mononuclear cells (PBMC) from non-smokers, smokers and COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…Gastrointestinal disorders 7 (50.0%) [12] 1 (50.0%) [ Hyperesthesia -------3 (75.0%) [6] 3 (11.5%) [6] Placebo SC (n = 10) Overall total 8 (80.0%) [25] 5 (100.0%) [21] 4 (100.0%) [22] 4 (100.0%) [25] 4 (100.0%) [ 4 (100.0%) [7] 4 (100.0%) [12] 4 (100.0%) [7] 1 (100.0%) [3] 18 (100.0%) [37] Injection-site discoloration One subject in the placebo group received a minimal amount of UTTR1147A instead of placebo due to a pharmacy error. This subject developed a small patch of mild erythema at the injection site, which completely resolved by study end.…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Gastrointestinal disorders 7 (50.0%) [12] 1 (50.0%) [ Hyperesthesia -------3 (75.0%) [6] 3 (11.5%) [6] Placebo SC (n = 10) Overall total 8 (80.0%) [25] 5 (100.0%) [21] 4 (100.0%) [22] 4 (100.0%) [25] 4 (100.0%) [ 4 (100.0%) [7] 4 (100.0%) [12] 4 (100.0%) [7] 1 (100.0%) [3] 18 (100.0%) [37] Injection-site discoloration One subject in the placebo group received a minimal amount of UTTR1147A instead of placebo due to a pharmacy error. This subject developed a small patch of mild erythema at the injection site, which completely resolved by study end.…”
Section: Safetymentioning
confidence: 99%
“…For example, IL‐22 has shown therapeutic benefits in mouse models of colitis, hepatitis, acute kidney injury, pancreatitis, and skin wound healing . IL‐22 may also support regeneration in other tissues, such as the thymus, and may protect against systemic bacterial infections originating in the lungs or intestines …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we evaluated the secretory antibody response, which plays an important role in restricting bacterial invasion through the mucosa. Apart from the secretory antibodies, cytokines produced by T helper-17 (Th17) and T helper-22 (Th22) cells have been shown to play important roles in protection against several S. pneumoniae strains [14][15][16][17]. Specifically, IL-17 and IL-22 produced by these cells together induce secretion of chemokines and antimicrobial peptides, as well as recruitment of neutrophils, which promote bacterial clearance [18].…”
mentioning
confidence: 99%
“…30 On the other hand, IL-22 has been linked to multiple pathologies of an inflammatory nature, for example, psoriasis and rheumatoid arthritis, in addition to having an important role in the defense of the lungs against pathogens, especially extracellular bacteria, assisting production and release, for example, of defensins in the mucosa of the airways, in addition to maintaining the integrity of the epithelium. 31 A study by Pichavant et al 31 showed that, during Streptococcus pneumoniae infections in mice exposed to cigar smoke, cytokine levels related to Th17 lymphocytes are decreased, leading to exacerbations. 33 In addition, IL-23 is associated with maintenance of the response generated by this group of cooperating T lymphocytes.…”
mentioning
confidence: 99%